2023
DOI: 10.1186/s12893-023-02214-0
|View full text |Cite
|
Sign up to set email alerts
|

Fully endoscopic microvascular decompression for the treatment of hemifacial spasm, trigeminal neuralgia, and glossopharyngeal neuralgia: a retrospective study

Weicheng Peng,
Rui Zhao,
Feng Guan
et al.

Abstract: Background Microvascular decompression (MVD) is already the preferred surgical treatment for medically refractory neurovascular compression syndromes (NVC) such as hemifacial spasm (HFS), trigeminal neuralgia (TN), and glossopharyngeal neuralgia (GPN). Endoscopy has significantly advanced surgery and provides enhanced visualization of MVD. The aim of this study is to analyze the efficacy and safety of fully endoscopic microvascular decompression (E-MVD) for the treatment of HFS, TN, and GPN, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The most frequent complications associated with MVD treatment for HFS are facial nerve paralysis and hearing loss, followed by instances of intracranial infection and wound-related issues, among others [ 20 , 21 ]. Peng et al [ 22 ] confirmed that fully endoscopic MVD surgery can reduce recurrence and complications, which is consistent with the results of this study. This may be because fully endoscopic MVD surgery has a better field of vision under the guidance of neuroendoscopy and can display the compression position more clearly through the high Telfon gasket, guiding the surgeon to rapidly and accurately relieve the compression.…”
Section: Discussionsupporting
confidence: 92%
“…The most frequent complications associated with MVD treatment for HFS are facial nerve paralysis and hearing loss, followed by instances of intracranial infection and wound-related issues, among others [ 20 , 21 ]. Peng et al [ 22 ] confirmed that fully endoscopic MVD surgery can reduce recurrence and complications, which is consistent with the results of this study. This may be because fully endoscopic MVD surgery has a better field of vision under the guidance of neuroendoscopy and can display the compression position more clearly through the high Telfon gasket, guiding the surgeon to rapidly and accurately relieve the compression.…”
Section: Discussionsupporting
confidence: 92%
“…The relapse rate in the endoscopic treatment group was 5% lower, while complications such as postoperative CSF leak were similar [28]. Peng et al [29] in 2023 described the following benefits of complete endoscopic treatment, which can be resumed in 4 points: (1) the different angles of the endoscope lens and the controlled depth of penetration of the endoscope provide a panoramic view of the cerebellopontine angle with 360 • assessment of the neurovascular conflict and avoiding the blind spots of traditional microscopy; (2) endoscopic visualization allows protector installation under direct visual control with circumferential positioning verification; (3) endoscopic decompression is possible without grinding away the petrosal tubercle; and (4) endoscope allows to assess the reliability of the installation of the protector after filling the cerebellopontine angle with cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 86%